2017
DOI: 10.3389/fpsyg.2017.00527
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison and Outcome Analysis of Patients with Takotsubo Cardiomyopathy Triggered by Emotional Stress or Physical Stress

Abstract: Background: Previous studies revealed that takotsubo cardiomyopathy (TTC) is triggered by physical and emotional stresses. This study was performed to determine the short- and long-term prognostic impact of emotional- and physical stress associated with TTC.Methods and results: Our institutional database constituted a collective of 84 patients diagnosed with TTC between 2003 and 2015. The patients were divided into two groups as per the presence of emotional stress (n = 24, 21%) or physical stress (n = 60, 52.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
0
10
1
1
Order By: Relevance
“…Interestingly, data derived from the International Takotsubo Registry revealed patients characteristics with TTC in the United States and Europe and showed that of 1,750 studied patients diagnosed with TTC 89.8% were postmenopausal women with a mean age of 66.8 years (5, 6). Importantly, higher in-hospital mortality rates of male TTC patients compared to female TTC patients have been observed retrospectively (11, 12). However, Patel et al found in their analysis no significant sex difference in respect of overall mortality rates of TTC patients aged ≥50 years (11).…”
Section: Epidemiology Of Takotsubo Cardiomyopathymentioning
confidence: 99%
“…Interestingly, data derived from the International Takotsubo Registry revealed patients characteristics with TTC in the United States and Europe and showed that of 1,750 studied patients diagnosed with TTC 89.8% were postmenopausal women with a mean age of 66.8 years (5, 6). Importantly, higher in-hospital mortality rates of male TTC patients compared to female TTC patients have been observed retrospectively (11, 12). However, Patel et al found in their analysis no significant sex difference in respect of overall mortality rates of TTC patients aged ≥50 years (11).…”
Section: Epidemiology Of Takotsubo Cardiomyopathymentioning
confidence: 99%
“…Atrial arrhythmias, on the other hand were prevalent in our study population, comprising 10.0% of the overall cohort. A recent metanalysis described the prevalence of atrial fibrillation in TTC ranging from 8.4 to 25.0%, depending upon the average age of the study population [15] , [25] , [26] , [27] , [28] , [29] . Acutely, atrial arrhythmias in TTC is thought to be the result of left atrial dysfunction as well as from a catecholaminergic surge [14] , [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Outra possível causa seria a miocardiopatia de Takotsubo, também chamada de miocardiopatia induzida por estresse, de insuficiência cardíaca aguda relativamente pouco conhecida. Ela mimetiza o diagnóstico de infarto agudo do miocárdio, sendo o diagnóstico final de 2% dos casos inicialmente atendidos com síndrome coronariana aguda 24 . A miocardiopatia de Takotsubo apresenta episódios de estresse psicológico como fator precipitante em cerca de 30% dos casos, sendo mais comum em mulheres e, assim como o câncer de mama, afeta predominantemente mulheres na pós-menopausa 24 .…”
Section: Mortalidade Cardiovascular Ligada Diretamente Ao Sobrediagnóunclassified